When Structure Mirrors Identity: Reading Noor Naga’s If an Egyptian Cannot Speak English as a Lyotardian Petit Récit - Arkan Naser Hussain (مجلة الباحث, 2025)
This paper explores Noor Naga’s If an Egyptian Cannot Speak English through the lens of Jean-François Lyotard’s concept of the petit récit, or “little narrative.” Instead of offering a tidy, overarching story, Naga’s novel breaks with conventional narrative expectations. It leans into fragmentation, using shifting voices, nonlinear time, metafiction, koans and footnotes. These formal choices do more than challenge aesthetic norms; they mirror the unstable, often contradictory nature of postcolonial identity itself. Rather than tying up its contradictions neatly, the novel embraces them, highlighting miscommunication, cultural dissonance, and unresolved tension. In doing so, it reflects Lyotard’s vision of postmodern ethics: storytelling that resists closure and values multiplicity. Here, fragmentation becomes not a flaw to be corrected, but a necessary and honest reflection of a fractured world